Ukraine`’s Bioenergy Sector: Trends and Perspectives for the Post-war Green Energy Transition - Kurbatova, Tetiana; Sotnyk, Iryna; Trypolska, Galyna; Gerlitz , Laima; Skibina, Tetiana; Prokopenko, Olha; Kubatko, Oleksandra (International Journal of Energy Economics and Policy, 2023)
The paper investigates trends in bioenergy development in Ukraine and its role in accelerating the green energy transition in the post-war period. The focus of the article is on the use of bioenergy resources for electricity generation, heat energy and liquid biofuel production. In this context, the potential of biomass, state support mechanisms, the results of their influence on bioenergy capacities deployment and the barriers restraining this sector development are considered. The study’s results proved that the inconsistency of the state policy and the failure to consider the specifics of energy production based on various bioenergy resources caused a significant lag in its development compared to other renewable energy technologies. With this in mind, the article systematizes strengths and weaknesses, opportunities and threats, and based on them, strategic recommendations for bioenergy development in Ukraine in the post-war period are developed.